Thalamic DBS with a constant-current device in essential tremor: A controlled clinical trial. (July 2017) - Wharen, Robert E.; Okun, Michael S.; Guthrie, Barton L.; Uitti, Ryan J.; Larson, Paul; Foote, Kelly; Walker, Harrison; Marshall, Frederick J.; Schwalb, Jason; Ford, Blair; Jankovic, Joseph; Simpson, Richard; et al.
Abstract: Introduction: This study of thalamic deep brain stimulation (DBS) investigated whether a novel constant-current device improves tremor and activities of daily living (ADL) in patients with essential tremor (ET). Methods: A prospective, controlled, multicenter study was conducted at 12 academic centers. We investigated the safety and efficacy of unilateral and bilateral constant-current DBS of the ventralis intermedius (VIM) nucleus of the thalamus in patients with essential tremor whose tremor was inadequately controlled by medications. The primary outcome measure was a rater-blinded assessment of the change in the target limb tremor score in the stimulation-on versus stimulation-off state six months following surgery. Multiple secondary outcomes were assessed at one-year follow-up, including motor, mood, and quality-of-life measures. Results: 127 patients were implanted with VIM DBS. The blinded, primary outcome variable (n = 76) revealed a mean improvement of 1.25 ± 1.26 points in the target limb tremor rating scale (TRS) score in the arm contralateral to DBS (p < 0.001). Secondary outcome variables at one year revealed significant improvements (p ≤ 0.001) in quality of life, depression symptoms, and ADL scores. Forty-seven patients had a second contralateral VIM-DBS, and this group demonstrated reduction in second-sided tremor at 180 days (p < 0.001). Serious adverse events related to the surgery included infection (n = 3), intracranial hemorrhage (n = 3), and device explantation (n = 3). Conclusion: Unilateral and bilateral constant-current VIM DBS significantly improves upper extremity tremor, ADL, quality of life, and depression in patients with severe ET. Highlights: A novel constant-current DBS device for patients with essential tremor. A prospective, controlled, multicenter study confirms the efficacy of thalamic DBS. Constant-current DBS may offer advantages over constant voltage devices.